Problematika dalam Evaluasi Studi Pembelajaran Pendidikan Islam - Ruqoiyah, Ruqoiyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2022)
Islamic educational institutions such as madrasas and Islamic boarding schools have succeeded in building human character with a religious culture that loves the Republic of Indonesia. The slanted view of informal institutions